Perkembangan Analisis Butir Pati dalam Kajian Arkeobotani di Indonesia - Arrozain, M. Dziyaul F. (JANUS, 2025)
The study of archaeobotany in Indonesia has progressed significantly over the past two decades. However, research based on starch grain analysis remains limited and less recognized. This article presents the development of starch grain analysis in Indonesia, utilizing data from archaeobotanical studies conducted between 2011 and 2024. The findings reveal that various extraction procedures, identification processes, and interpretations of starch grains have contributed to understanding the past relationship between humans and plants. Moreover, these aspects have also contributed to the development of starch grain analysis trends, including methodological development and diversification phases. However, starch analyses still face limitations, including restricted geographical scope, disparities in cultural period coverage, and insufficient reference sample databases. Addressing these limitations promptly is crucial to facilitate more comprehensive and accelerated advancements in starch grain analysis in the future. === Kajian arkeobotani di Indonesia berkembang pesat dalam dua dekade terakhir. Namun, kajian arkeobotani yang berbasis butir pati masih relatif sedikit dilakukan dan kurang banyak diketahui. Artikel ini memaparkan perkembangan analisis butir pati yang telah dilakukan di Indonesia melalui kajian literatur. Data yang digunakan berupa hasil penelitian arkeobotani yang menganalisis butir pati dari tahun 2011 hingga 2024. Hasil riset menunjukkan bahwa ragam prosedur ekstraksi, proses identifikasi, dan interpretasi butir pati berhasil menarasikan relasi manusia dan tumbuhan di masa lalu. Selain itu, ketiganya juga menghasilkan tren perkembangan keilmuan analisis butir pati berupa fase perkembangan metode dan fase diversifikasi kajian. Namun demikian, analisis butir pati yang telah dilakukan masih menyisakan keterbatasan berupa cakupan wilayah kajian, kesenjangan cakupan periodisasi situs, dan keterbatasan database sampel referensi. Limitasi tersebut perlu segera diperbaiki agar analisis butir pati dapat berkembang lebih pesat lagi di masa yang akan datang.